The Implementation of Multi-Objective Optimization on the Basis of Ratio Analysis Method to Select the Lecturer Assistant Working at Computer Laboratorium - Limbong, Tonni; Simarmata, Janner; Sriadhi, S; R S Tambunan, A; Keristiana Sinaga, Enny; Simbolon, Naeklan; M P Simarmata, H; L S Siahaan, A; Ruth Septarini, Indira; Kelana Jaya, Indra; Arafat Lubis, Maulana; Khairi Siregar, Ilham; et al. (International Journal of Engineering and Technology, 2018)
A lecturer assistant is expected to be professional when dealing with the score or decision. Being professional, the lecturer assistant will be constantly respected by the students. The lecturer assistant should be able to make use of the time to keep the disciplinary. Selecting and determining the lecturer assistant at Computer Science of Unika St. Thomas Medan are conducted by the phases of selecting and taking value of the test score, the semester of lecturer assistant candidate, the number of classes to be assisted, cumulative grade point achievement, and the score of the assisted course. The Method of Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) is in the part of Decision Support System introduced by Brauers dan Zavadkas. This method is the multi-objective optimization technique which is successfully applied to solve the various complicated decision-making and well-used in terms of lecturer assistant selection due to its simple calculation and easiness to understand.Â Â